(untitled) (Bangladesh Journal of Scientific Research, 2016)
The Pourashava area of Manikganj, located in the central part of Bangladesh is treated as arsenic hotspot in the country as the outcome of various studies concludes that almost 80% of the domestic tube wells at this area exceed arsenic level of Bangladesh standard (50 ?g/l) for drinking water. To enhance the potable water supply in the area, 15 geoelectric soundings survey using Schlumberger configuration with spreading AB/2 = 300 meters has been executed to decipher the subsurface lithology distribution and aquifers at different depths, to determine the lateral and vertical extent of aquifer at the area. Correlation of the analyzed VES results with primary and secondary borelogs, the subsurface sequence of the area is broadly divided into two geoelectric units. Firstly, the near surface geoelectric unit of resistivity less than 20.0 ?-m represents the top soil composed of silty clay to clay. The thickness of this layer varies from 1 meter to 5 meters. The second geoelectric unit represents the sand layer and is characterized by a resistivity range of 21.0 to 190.0 ?-m. This unit encompasses the very fine sand with variable thickness of 2 to 248m while resistivity is from 21.0 to 30.0 ?-m, very fine to fine sand having thickness from 174-280m and geoelectric value ranges from 31.0 to 40.0 ?-m, fine sand with resistivity from 44.0 to 50.0 ?-m, fine to medium sand having resistivity from 51.0 to 70.0 ?-m, medium sand and medium to coarse sand with resistivity value 75.0 to 110.0 ?-m, and 140.0 to 190.0 ?-m, respectively. The ultimate thickness of this unit could not be determined due to limited spread of survey but at least continues to a depth of 300 m. In the context of groundwater storage, the second geoelectric unit acts as the regional aquifer and is used for groundwater development in the Pourashava area for water supply. Bangladesh J. Sci. Res. 27(2): 109-120, December-2014